Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4238/2014.march.24.10
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation of the P16, MGMT, and hMLH1 genes in combination with the methylenetetrahydrofolate reductase C677T genetic polymorphism and folate intake in gastric cancer

Abstract: ABSTRACT. Epidemiological studies have indicated that folate metabolism is correlated with increased risk of gastric cancer. Since methylenetetrahydrofolate reductase (MTHFR) is an important enzyme involved in folate metabolism, in this study, we examined whether polymorphisms and haplotypes of MTHFR are correlated with the risk of gastric cancer. The polymorphisms MTHFR C677T and MTHFR A1298C were genotyped by polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) analysis in 285 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…It is noteworthy to mention that con icting results have been reported on the in uence of the MTHFR C677T polymorphism on precancerous lesions or cancer. Some studies have shown an increased risk of gastric cancer development among Asians and Caucasians [12,26], while others studies have reported a negative association or null results [27,28]. Con icting results indicate that population-speci c and geographical factors may account for this phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…It is noteworthy to mention that con icting results have been reported on the in uence of the MTHFR C677T polymorphism on precancerous lesions or cancer. Some studies have shown an increased risk of gastric cancer development among Asians and Caucasians [12,26], while others studies have reported a negative association or null results [27,28]. Con icting results indicate that population-speci c and geographical factors may account for this phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“… 23 However, other articles showed exactly opposite results about these two polymorphisms. 24 , 25 There are still many controversial results in other cancer types, including prostate cancer, bladder cancer, head and neck cancer, leukemia and lymphoma, nervous system cancers, etc. 26 31 …”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated the effects of genetic polymorphisms related to one‐carbon metabolism on the risk of gastric cancer. However, most of these studies have focused on polymorphisms of the MTHFR , MTR , and MTRR genes , and the results are variable. Such inconsistent results in terms of gastric cancer might be explained by gene–diet interactions.…”
Section: Introductionmentioning
confidence: 99%